Case report: Successful treatment of ulcerative colitis-related post-colectomy enteritis refractory to multiple therapies with ustekinumab - Guo, Chenglin; He, Shengduo; Wang, Huahong (Frontiers in Immunology, 2024)
Ulcerative colitis-related severe post-colectomy enteritis is a rare condition. A few cases have undergone successful treatment with corticosteroids, Cyclosporine , Azathioprine , and Infliximab. We aim to evaluate the treatment outcome of ustekinumab in this rare case. Here we describe a 56-year-old woman with post-colectomy enteritis refractory to multiple therapies. Finally, the patient was administered with ustekinumab treatment. Under monitoring, the feces volume of the patient decreased from 5000-7000 mL per day to 1700-2000 mL. Over a one-year follow-up period, the patient gradually gained body weight, with the stoma drainage of formed brown stool. And the villi of the small intestinal mucosa restore growth. To our knowledge, this is the first report that indicates ustekinumab could be a treatment selection for ulcerative colitis-related severe post-colectomy enteritis.